Characterizing the foreshock, main shock, and aftershock sequences of the recent major earthquakes in Southern Alaska, 2020–2024 - Filippova, A.; Fomochkina, A.; Kossobokov, V.; Nekrasova, A. (Frontiers in Earth Science, 2025)
We continue analyzing earthquake sequences in terms of their variability and scaling properties, including the behavior of the control parameter η of the unified scaling law for earthquakes (USLE), along with a detailed analysis of the surface wave records for reconstruction of the source in approximation of the second moments of the stress glut tensor to obtain integral estimation of its length, orientation, and seismic process development over time. In particular, we present the analysis of the cases of the four recent earthquakes in Southern Alaska – 22 July 2020, Mw 7.8 at 105 km SSE of Perryville, 19 October 2020, Mw7.6 at 97 km SSE of Sand Point, 29 July 2021, Mw 8.2 at 99 km SE of Perryville and 16 July 2023, Mw7.2 at 106 km S of Sand Point that have occurred right at the western edge of the rupture zone of the 1964 Great Alaska, M9.3 mega-earthquake and contribute to apparent activation of the region started with the three major earthquakes (24 January 2016, Mw7.1, 23January 2018, Mw7.9, and 30 November 2018, Mw7.1) at its north and southern borders.